Understanding the antimicrobial and antioxidant potential of bioinspired platinum nanoparticles synthesized using ocimum tenuiflorum - Varma, Sanjana; Bamb, Aagam Lalit; Tambe, Sayali A.; Burade, Dimpal K.; Jagdale, Swati; Pande, Bharat; Vamkudoth, Koteswara Rao; Chaudhari, Bhushan P. (BioNanoScience, 2025)
The emergence of infectious diseases has highlighted the need for novel and effective antimicrobial agents. Platinum nanoparticles (PtNPs) could act as a potent antimicrobial agent due to their unique physicochemical properties. However, the chemical or physical synthesis methods of PtNPs have drawbacks, like irregular shape and use of toxic chemicals. These drawbacks can be effectively overcome by using the biological method synthesis. Thus, this study presents the green synthesis of platinum nanoparticles (PtNPs) using Ocimum tenuiflorum leaf extract as a bio-reductant. The study also comprehensively encompasses the role of multiple process parameters for the green synthesis of PtNPs. The high-resolution transmission electron microscopy (HR-TEM) revealed spherical PtNPs with an average size of 2.36 ± 0.5 nm that exhibits excellent stability (zeta potential, −45.67 ± 2.57 mV). Phytochemical analysis of aqueous O. tenuiflorum leaf extract was performed to assess the bioactive compounds like saponins, phenols, and tannins, reducing sugars and flavonoids. The PtNPs demonstrated significant antioxidant activity of 86.9 ± 0.12% at 10 µg/mL. Further, the biosynthesized PtNPs showed efficient antimicrobial activity with a minimum inhibitory concentration (MIC) of 6.25 µg/mL against Escherichia coli and 1.5 µg/mL against Staphylococcus aureus. These findings highlight the therapeutic potential of eco-friendly PtNPs for pharmaceutical and biotechnological applications.